Over-accumulation of abscisic acid in transgenic tomato plants increases the risk of hydraulic failure - Lamarque, Laurent J.; Delzon, Sylvain; Toups, Haley; Gravel, Anne‐Isabelle; Corso, Déborah; Badel, Eric; Burlett, Régis; Charrier, Guillaume; Cochard, Hervé; Jansen, Steven; King, Andrew; Torres‐Ruiz, José M.; et al. (Wiley, 2019)
Climate change threatens food security, and plant science researchers have investigated methods of sustaining crop yield under drought. One approach has been to overproduce abscisic acid (ABA) to enhance water use efficiency. However, the concomitant effects of ABA overproduction on plant vascular system functioning are critical as it influences vulnerability to xylem hydraulic failure. We investigated these effects by comparing physiological and hydraulic responses to water deficit between a tomato (Solanum lycopersicum) wild type control (WT) and a transgenic line overproducing ABA (sp12). Under well-watered conditions, the sp12 line displayed similar growth rate and greater water use efficiency by operating at lower maximum stomatal conductance. X-ray micro-tomography revealed that sp12 was significantly more vulnerable to xylem embolism, resulting in a reduced hydraulic safety margin. We also observed a significant ontogenic effect on vulnerability to xylem embolism for both WT and sp12. This study demonstrates that the greater water use efficiency in the tomato ABA overproducing line is associated with higher vulnerability of the vascular system to embolism and a higher risk of hydraulic failure. Integrating hydraulic traits into breeding programs represents a critical step for effectively managing a crop’s ability to maintain hydraulic conductivity and productivity under water deficit.
Keywords: Xylem embolism; tomato; water deficit; abscisic acid; hydraulic failure; transgenic line; crop; drought